Polarizability of Kekulene, Septulene, and Nearest Non-Planar Polycyclic Aromatic Hydrocarbons - Timur Lukmanov; Arslan F. Akhmetov; Denis Sh. Sabirov (C, 2022)
The polarizability of polycyclic aromatic hydrocarbons (PAHs) is an important property that relates to their abundance in natural environments. To assess the differences in the mean polarizability of planar and non-planar polycyclic aromatic hydrocarbons (PAHs), we computationally studied the PAH series of circulenes (kekulene C48H24, [13]circulene C52H26, and septulene C56H28), a number of the nearest helicenes, and their “expanded” isomers. We mean under “nearest” a close number of aromatic rings: 11 (C46H26), 12 (C50H28), 13 (C54H30), and 14 (C58H32). For these PAHs, we performed the quantum chemical calculations of thermodynamic and polarizability parameters with the PBE/3ζ density functional theory method, which is widely used in the theoretical chemistry of fullerenes and PAHs. The calculated mean polarizabilities (in Å3) ranged from 80.1 for [11]helicene to 135.5 for septulene, and while the circulenes and expanded helicenes had similar values, the mean polarizability of the normal helicenes was markedly lower. In all four pairs of helical PAHs, the expanded helicene was energetically considerably more favorable than its standard helicene isomer. Herewith, the ratio of their polarizabilities was equal to 1.3.